2013
DOI: 10.1155/2013/952375
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mediators of Neuroinflammation in the Pathogenesis of Parkinson’s Disease

Abstract: Neuroinflammation is a host-defense mechanism associated with restoration of normal structure and function of the brain and neutralization of an insult. Increasing neuropathological and biochemical evidence from the brains of individuals with Parkinson's disease (PD) provides strong evidence for activation of neuroinflammatory pathways. Microglia, the resident innate immune cells, may play a major role in the inflammatory process of the diseased brain of patients with PD. Although microglia forms the first lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(160 citation statements)
references
References 143 publications
3
154
0
3
Order By: Relevance
“…Once thought to be only a consequence of motor neuron death, neuroinflammation is now established as an important factor not only in the pathogenesis of ALS, but also in many other neurodegenerative diseases, including Parkinson's, Alzheimer's, multiple sclerosis, HIV-associated encephalopathy, and cerebrovascular disease [46][47][48][49][50][51]. Much of what has been learned in ALS regarding neuroinflammation has come through discoveries in these other neurodegenerative diseases.…”
mentioning
confidence: 99%
“…Once thought to be only a consequence of motor neuron death, neuroinflammation is now established as an important factor not only in the pathogenesis of ALS, but also in many other neurodegenerative diseases, including Parkinson's, Alzheimer's, multiple sclerosis, HIV-associated encephalopathy, and cerebrovascular disease [46][47][48][49][50][51]. Much of what has been learned in ALS regarding neuroinflammation has come through discoveries in these other neurodegenerative diseases.…”
mentioning
confidence: 99%
“…Some studies revealed that one of the mechanisms of dopaminergic degeneration is through neuroinflammatory mediators [30,31]. The proinflammatory cytokines and cells play crucial role in the damage of vulnerable dopaminergic cells.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has shown an increase in infiltrating peripheral cells in the SN of PD patients (31), and PBMC composition and function are reportedly altered in PD patients (32)(33)(34)(35)(36). To ensure that our observed differences in p11 levels were not related to PBMC composition changes, we also quantified leukocyte composition.…”
Section: Discussionmentioning
confidence: 99%